Integrated Extensible Simulation Platform for Vehicular Sensor Networks in Smart Cities. (13th December 2012) - Tang, Xiaolan; Pu, Juhua; Cao, Ke; Zhang, Yi; Xiong, Zhang
Abstract : This paper presents an integrated extensible simulation platform BHU-VSim for vehicular sensor networks (VSNs), which aims to support general simulation environment for typical vehicular applications in smart cities. To deploy urban traffic scenario, we propose a hierarchical object structure to manage entities with different movement models in the network. Furthermore, we design a general data container to present different kinds of data transferred and provide two schemes to generate data packages. Regarding transmission control, the platform includes three components: task scheduling, storage management, and routing deployment. We support importing external routing protocols and configuring relevant parameters to satisfy various transmission requirements. Finally, an instance application, real-time traffic monitoring, and an example of statistical analysis are introduced to prove the practicality and accuracy of the simulator. In one word, as an initiate attempt, our platform provides significant improvement of VSNs' simulations.